2018
DOI: 10.1093/aje/kwy225
|View full text |Cite|
|
Sign up to set email alerts
|

Association Between Maternal Iodine Intake in Pregnancy and Childhood Neurodevelopment at Age 18 Months

Abstract: There are limited and inconsistent data suggesting that mild iodine deficiency in pregnancy might be associated with poorer developmental outcomes in children. Between 2011 and 2015, we conducted a prospective cohort study in Australia examining the relationship between maternal iodine intake in pregnancy and childhood neurodevelopment, assessed using Bayley Scales of Infant and Toddler Development, Third Edition (Bayley-III), in 699 children at 18 months. Maternal iodine intake and urinary iodine concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(63 citation statements)
references
References 23 publications
4
59
0
Order By: Relevance
“…What was less expected was the finding that omega‐3 supplementation of women with replete omega‐3 status appears to increase risk of early preterm birth. Similar patterns have been seen for several micronutrients and higher risks of adverse health outcomes for both low and high nutrient intakes—a U‐shaped relation . Although of different design and size compared with ORIP, a secondary analysis of a prenatal omega‐3 supplementation RCT suggests that for women at risk of recurrent preterm birth, the probability of preterm birth was highest at low and high intakes, and lowest with moderate fish consumption …”
Section: Discussionmentioning
confidence: 55%
“…What was less expected was the finding that omega‐3 supplementation of women with replete omega‐3 status appears to increase risk of early preterm birth. Similar patterns have been seen for several micronutrients and higher risks of adverse health outcomes for both low and high nutrient intakes—a U‐shaped relation . Although of different design and size compared with ORIP, a secondary analysis of a prenatal omega‐3 supplementation RCT suggests that for women at risk of recurrent preterm birth, the probability of preterm birth was highest at low and high intakes, and lowest with moderate fish consumption …”
Section: Discussionmentioning
confidence: 55%
“…The publication made by Zhou and Condo has shown impaired psychomotor development of children at 18 months of age, assessed on the Bayley-III scale, both in case of supplementing too low (< 220 mcg/day) and too high (> 391 mcg/day) iodine doses before 20 weeks of gestation [49].…”
Section: Iodinementioning
confidence: 99%
“…Approximately 80% of Australian women now consume perinatal supplements, many of which contain small doses of DHA. 26 Although we excluded women who were taking more than 150 mg of DHA per day, we enrolled more than 700 women who were known to have been regularly consuming a low dose of DHA (≤150 mg per day). This may have influenced the baseline level of DHA among the women included in the ORIP trial, which was about 20% higher than that observed in the Kansas University DHA Outcomes Study (KUDOS), in which a significantly lower rate of early preterm delivery was observed with n−3 supplementation than with placebo.…”
Section: Discussionmentioning
confidence: 99%